Suicidality and Quality of Life in Treatment-Resistant Depression Patients in Latin America: Secondary Interim Analysis of the TRAL Study - Corral, Ricardo; Alessandria, Hernan; Agudelo Baena, Lina María; Ferro, Eugenio; Duque, Xochitl; Quarantini, Lucas; Caldieraro, Marco Antonio; Cabrera, Patricia; Kanevsky, Gabriela (Frontiers in Psychiatry, 2022)
Background A large proportion of patients with major depressive disorder (MDD) have treatment-resistant depression (TRD). The TRAL study examines the impact of TRD on suicidality and health-related quality of life (HRQoL) among MDD patients in 4 Latin American countries. Methods In this multicenter, prospective, observational study, MDD patients were recruited from 33 sites in Mexico, Colombia, Brazil, and Argentina. Patients were assessed for TRD, defined as failure to respond to ≥2 antidepressant medications of adequate dose and duration. Other assessments included current disease status, Mini International Neuropsychiatric Interview (MINI), Columbia-Suicide Severity Rating Scale (C-SSRS), 5 Level EQ-5D (EQ-5D-5L), Patient Health Questionnaire-9 (PHQ-9), and Sheehan Disability Scale (SDS). Results 1,475 MDD patients were included in the analysis (mean age, 45.6 years; 78% women), and 429 met criteria for TRD. Thoughts of suicide and suicide attempts were more common among TRD patients (38.7%) compared with non-TRD patients (24.9%; P < 0.0001), according to the current disease status questionnaire. The C-SSRS showed that lifetime suicidal behavior was significantly more common among TRD patients than non-TRD patients (13.8 vs. 10.0%; P = 0.0384). Compared with non-TRD patients, TRD patients showed significantly greater adverse impacts on QoL (EQ-5D-5L), more severe depression (PHQ-9), and greater functional impairment (SDS). Conclusion TRD patients in clinical sites from Mexico, Colombia, Brazil, and Argentina were more likely to experience suicidality and negative effects on HRQoL than non-TRD patients.